Peran Tokoh Agama Dalam Meningkatkan Religiusitas Warga Desa Giri, Kabupaten Gresik Di Masa Pandemi Covid-19 - Andini Nurrahmah Dewi; Agus Machfud Fauzi (Universitas Islam Negeri Imam Bonjol Padang, 2021)
The Covid-19 pandemic in Indonesia is causing many changes in all areas of life both political, religious, social, economic and cultural. The increasing number of positive cases indicates that Covid-19 is a non-natural disaster that should be watched by the whole community. In the current pandemic situation, religious leaders in Giri Village play an important role in inviting villagers to continue to try to implement health protocols and worship God. This study aims to find out and analyze the role of religious figures in Giri Village in improving the religiosity of citizens during the Covid-19 Pandemic. This study uses descriptive qualitative method by observing directly at the research site and conducting interviews on several informants. This study uses the functional structure theory of Talcott Parsons which states that everyone has their own role and function in society which is a system. This study found that people can follow the direction of religious leaders who have a role in improving the worship activities of citizens. The National Covid-19 Task Force has the slogan